Respuesta :
[tex]2x^4(4x^2 + 3x + 1)=\\\\(2x^4)(4x^2)+(2x^4)(3x)+(2x^4)(1)=\\\\8x^6 + 6x^5+2x^4[/tex]
The answer is A.
The answer is A.
Answer:
The product of the [tex]2x^{4}(4x^{2}+3x+1)[/tex] is [tex]8x^{6}+6x^{5}+2x^{4}[/tex] .
Step-by-step explanation:
As given the expression in the question be
[tex]= 2x^{4}(4x^{2}+3x+1)[/tex]
First open the bracket
[tex]= 2x^{4}\times 4x^{2}+2x^{4}\times 3x+2x^{4}\times 1[/tex]
Now by using the property
[tex]x^{a}\times x^{b}=x^{a+b}[/tex]
[tex]= 8x^{6}+6x^{5}+2x^{4}[/tex]
Therefore the product of the [tex]2x^{4}(4x^{2}+3x+1)[/tex] is [tex]8x^{6}+6x^{5}+2x^{4}[/tex] .